Application of Eco-Enzyme Solution as A Multipurpose Liquid Fertilizer to Enhance Performance of Sorghum Varieties - Irmansyah, T.; Simangunsong, Alwan Alawi; Sebayang, Amelia; Girsang, Setia Sari; Lubis, Dini Sahfitri (agriTECH, 2024)
Eco-enzyme, derived from various household wastes such as vegetables, fruits, or fruit peel, is an organic fertilizer rich in essential nutrients for plant growth. Therefore, this study aimed to investigate the impact of eco-enzyme concentrations on the growth and yield of several sorghum cultivars (Sorghum bicolor (L.) Moench) in Tanjung Sari, Medan Selayang Subdistrict, Medan from June to September 2021. To achieve this objective, a Randomized Block Design (RBD) comprising 2 factors, namely eco-enzyme concentration (T0:0 mL/L, T1:9.3 mL/L, T2: 18.6 mL/L, and T3: 27.9 mL/L) and sorghum varieties (S1: Super 1, S2: Super 2, S3: Suri 4) was adopted. Eco-enzyme solution consisted of molasses, fruit peels (watermelon, cucumber, and orange), and water. The results showed that the interaction between Suri 4 and a concentration of 27.9 mL/L affected sorghum production. Each ecoenzyme and the varieties affected stem diameter (24.93 mm and 22.66 mm), flowering time (59.19 DAP and 56.00 DAP), as well as wet (631.03 g and 410.20 g) and dry stove weights (315.52 g and 205.10 g). Consequently, the application of eco-enzyme at a concentration of 27.9 mL/L enhances both the growth and yield of sorghum.